Taxonomic and Functional Patterns of Benthic Communities in Southern Temperate Tidal Flats - Lam-Gordillo, Orlando; Baring, Ryan; Dittmann, Sabine (Frontiers in Marine Science, 2021)
Coastal ecosystems are vulnerable to anthropogenic disturbances which can cause loss of benthic macrofauna and their ecosystem functioning. Despite the importance of functional assessments for conservation and management, knowledge gaps persist on the generality of how the diversity and functional traits of benthic communities influence ecosystem functioning. We investigated eight sites in three different habitats across ~1,260 km of coastline, to evaluate patterns between taxonomic and functional diversity of benthic macrofauna, and the relationship between benthic macrofauna, functional traits and environmental conditions. A total of 74 benthic macrofauna taxa were identified. Significant differences across sites and season were found for metrics based on taxonomic and functional traits. Multivariate analysis revealed spatial-temporal differences, which were more evident based on taxa than functional traits. Functional diversity also showed spatial and temporal differences and was positively correlated with the number of taxa. The dominant functional traits modalities were deposit feeders, with large (>20 mm) body size, burrowers, bioirrigators, deeper than 3 cm in sediments, and irregular morphology. Novel Generalized Linear Latent Variable Models (GLLVM) uncovered several site-dependent relationships between taxa, traits and environmental conditions. Functional redundancy was lowest in a highly modified lagoon, and highest in a more pristine embayment. The outcomes from this study showed site-dependent patterns of benthic communities based on either taxonomic or functional metrics, highlighting that both perspectives are complementary to obtain a holistic understanding of the functioning in marine sediments under environmental change.